Studi Aksesibilitas Halte Bis Trans Menuju Lingkungan Inklusif (Universitas Islam Negeri Sunan Ampel Surabaya, 2017)
The provision of an inclusive environment was one of Sustainable Development Goals (SDG) 11 targets that was also listed in the declaration document of the 2016 NUA (New Urban Agenda) Habitat III. This was no exception for the public buildings and transport facilities provision that should meet and accommodate the needs of all users including persons with disabilities, the elderly, children, and women. Currently, Indonesia has committed to ratify and implement the CRPD, including the enactment of several regulations and the provision of access environment in public buildings. However, such implementation has not been maximized and complies with standards based on inclusion design. This paper is part of a Research-Based-Community Service to observe and evaluate bus stop and the pedestrian way in Surabaya. Yet, the discussion only highlights the result of pre-eliminary study of accessibility condition at bus stop based user paricpation. Methods of observation and environmental simulation were used to obtain research data. The results show various problems caused by lack of user participation and understanding and information on the design of accessible environment. This led to many application designs on the environment not in accordance with existing regulations and the needs of users especially those with special needs.